2021
DOI: 10.1080/09669760.2021.1956440
|View full text |Cite
|
Sign up to set email alerts
|

Fun and the benefits of Sign Supported Big Books in mainstream Indonesian kindergartens

Abstract: Inclusive kindergarten provision remains relatively rare in Indonesia. This article indicates factors that contribute to this situation (stigmatisation, lack of resources and training) and reports on an approach to begin to address it. Sign Supported Big Books were evaluated in mainstream kindergartens (i.e. classes without children with special educational needs) as a way of enhancing their inclusive affordances. These books used Signalong Indonesia, a keyword signing approach, to support whole class stories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Teachers (70%) disagreed with the statement the approach didn't help children to understand that the story and 93% of teacher believed that the approach helped children to remember the stories. This supports findings from the pilot study, which found that children had improved comprehension and recall of stories with SSBBs, and that teachers and children found the approach fun (Rofiah et al, 2023).…”
Section: Findings and Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Teachers (70%) disagreed with the statement the approach didn't help children to understand that the story and 93% of teacher believed that the approach helped children to remember the stories. This supports findings from the pilot study, which found that children had improved comprehension and recall of stories with SSBBs, and that teachers and children found the approach fun (Rofiah et al, 2023).…”
Section: Findings and Discussionsupporting
confidence: 84%
“…As their name indicates they are big, around 34×42 cm, and have large story illustrations that help teachers to engage the interest of young children (Jayendra et al, 2018a) and support interactive, dialogic, storytelling (Lever and Sénéchal, 2011). Rofiah and colleagues (Rofiah et al, 2023) created big books with a Signalong Indonesia sign for each page of the story. These Sign Supported Big Books (SSBB) featured a single visual sign prompt on the back of each page for the teacher when telling the story to the class.…”
Section: Sign Supported Big Booksmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indonesia, establishing an inclusive education system across Indonesia is a social undertaking that is especially difficult. Indonesia, whose national motto is Bhinneka Tunggal Ika ('unity in diversity,') is the world's largest archipelagic country with more than 17, 524 islands and a population of more than 270 million people, making it the world's most diverse multi-ethnic state [2].…”
Section: Introductionmentioning
confidence: 99%